Fistula Champions leading local actions for Ending Fistula in Bangladesh - Karmakar, Aysarjo; Karmakar, Anirudha; Huda, Sk Nazmul (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To document how fistula champions are contributing to improving maternal health, prevention of female genital fistula in remote villages in Bangladesh and their achievements to date. Methods: Eight girls grade IX and X from three remote villages of Satkhira district were enrolled in School Girls for Fistula Free Bangladesh. They had four hours orientation workshop on obstetric fistula. They were provided a checklist for community actions for fistula awareness and prevention. The school girls prepared social maps of the villages, identified local resources and institutions for prevention of early marriage and promotion of safe motherhood. Activities included listing all pregnant women in their communities and educating them for pregnancy and labor care. Results: The school girls identified 54 pregnant women in the villages; these women received 127 ANC visits, 23 deliveries took place in hospitals. There were no incidents of early marriage in the villages. The school girls met the benchmarks to be a fistula champion and were awarded certificates for achievements. Conclusions: Fistula champions have set up a model for local actions for ending fistula in remote communities.